MON-521 Impact of Chronic Hypoparathyroidism on Health-Related Quality of Life: Findings from a 13-Country Patient Survey - Siggelkow, Heide (J Endocr Soc, 2019)
Significant knowledge gaps exist regarding the humanistic effects of hypoparathyroidism (HypoPT), a rare debilitating disorder. We report results from a global survey (13 countries) to characterize the impact of HypoPT on health-related quality of life (HRQoL) from the patient perspective. An anonymous survey was conducted in patients with uncontrolled chronic HypoPT (as determined by patients’ report of persistent symptoms and/or poorly controlled calcium levels as told by their physician) despite receiving conventional therapy. Patients currently or previously treated with parathyroid hormone were excluded. HRQoL and health status were evaluated using 2 validated instruments, 36-item short form health survey (SF-36) and 5-level EuroQoL 5 dimensions (EQ-5D-5L). All analyses were descriptive. Survey was conducted Oct 2017─Mar 2018 in 398 patients who met the study inclusion criteria (mean age, 51.7 years; women, 78%; surgery as main cause of HypoPT, 80%; mean duration of HypoPT, 8.9 years). There was an apparent inverse relationship between HypoPT symptom severity and both HRQoL assessment scores - the greater the severity, the lower the HRQoL and health status scores. Mean EQ-5D-5L utility scores (0-1) were 0.9/0.8/0.7/0.4 for patients reporting no/mild/moderate/severe HypoPT symptoms, respectively. EQ-5D-5L visual analog scale scores (0-100) were 86.9/72.5/57.7/41.1 for patients reporting no/mild/moderate/severe HypoPT symptoms, respectively. Mean SF-36 summary scores (0‒100) were 45.4/44.6/37.1/28.7 (physical component summary) and 53.2/44.9/35.2/31.6 (mental health component summary) for patients reporting no/mild/moderate/severe HypoPT symptoms, respectively. Findings showed that despite receiving conventional treatment, HypoPT was associated with burdensome symptoms that negatively affected HRQoL and health status. The degree of HRQoL reduction reflects the magnitude of symptom severity reported by patients with chronic HypoPT. SF-36 scores (mental and physical) reported for HypoPT patients in this survey were generally lower than scores reported in literature for patients with other disease states, such as heart disease, hematologic disorders, diabetes, or cancer. Funding: Shire